Professional Discretion and the Predictive Validity of a Juvenile Risk Assessment Instrument: Exploring the Overlooked Principle of Effective Correctional Classification - McCafferty, James T. (Youth violence and juvenile justice, 2017)
The ability for professionals to override the results of an actuarial risk assessment tool is an essential part of effective correctional risk classification; however, little is known about how this important function affects the predictive validity of these tools. Using data from a statewide sample of juveniles from Ohio, this study examined the impact of professional adjustments on the predictive validity of a juvenile risk assessment instrument. This study found that the original and adjusted risk levels were significant predictors of recidivism, but the original risk levels were stronger predictors of recidivism than the adjusted risk levels that accounted for overrides.